2020
DOI: 10.3174/ajnr.a6439
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Puncture: Creation and Resident Acceptance of a Low-Cost, Durable, Reusable Fluoroscopic Phantom with a Fluid-Filled Spinal Canal for Training at an Academic Program

Abstract: Simulation-based medical training provides learners a method to develop technical skills without exposing patients to harm. Although fluoroscopic phantoms are already adopted in some areas of radiology, this has historically not been for lumbar puncture. Commercially available phantoms are expensive. We report a cost-effective, accessible solution by creation of an inexpensive phantom for resident training to perform fluoroscopically guided lumbar puncture, as well as instructions on how to make a phantom for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Training can be improved by leveraging video-based or simulationbased training (using either phantoms 87 or virtual-reality devices), which are increasingly being evaluated and adopted in adult neurology settings. [72][73][74][75][76][88][89][90][91][92][93] Studies have consistently found that such training aids are effective and can improve operator confidence, an important finding considering that medical students or junior doctors often report a lack of confidence in performing the procedure, 94,95 and operator stress has been associated with reduced patient confidence in the operator and an increased risk of post-LP headache in patients. 96 Evidence that these benefits can translate into improved performance in clinical practice comes from a study involving 110 junior doctors with no previous experience performing LPs.…”
Section: Emerging Techniques and Innovations In Lpmentioning
confidence: 99%
See 1 more Smart Citation
“…Training can be improved by leveraging video-based or simulationbased training (using either phantoms 87 or virtual-reality devices), which are increasingly being evaluated and adopted in adult neurology settings. [72][73][74][75][76][88][89][90][91][92][93] Studies have consistently found that such training aids are effective and can improve operator confidence, an important finding considering that medical students or junior doctors often report a lack of confidence in performing the procedure, 94,95 and operator stress has been associated with reduced patient confidence in the operator and an increased risk of post-LP headache in patients. 96 Evidence that these benefits can translate into improved performance in clinical practice comes from a study involving 110 junior doctors with no previous experience performing LPs.…”
Section: Emerging Techniques and Innovations In Lpmentioning
confidence: 99%
“…Traditionally, physicians have learned to perform LP through unstructured observation and supervision during medical training. Training can be improved by leveraging video‐based or simulation‐based training (using either phantoms 87 or virtual‐reality devices), which are increasingly being evaluated and adopted in adult neurology settings 72–76,88–93 . Studies have consistently found that such training aids are effective and can improve operator confidence, an important finding considering that medical students or junior doctors often report a lack of confidence in performing the procedure, 94,95 and operator stress has been associated with reduced patient confidence in the operator and an increased risk of post‐LP headache in patients 96 .…”
Section: Emerging Techniques and Innovations In Lpmentioning
confidence: 99%
“…14,15,20 The multi-material feature can allow regions of varying radiopacity, improving the realism of anatomical models when X-ray imaged. 3D printed anatomical models are used for simulating procedures under fluoroscopy, for example lumbar puncture, 21 cardiac catheterisation 22 or screw placement. 23 These simulators could be further improved by introducing radiopaque resin for multi-material 3D printing.…”
Section: Introductionmentioning
confidence: 99%